PDGFR-β modulates vascular smooth muscle cell phenotype via IRF-9/SIRT-1/NF-κB pathway in subarachnoid hemorrhage rats. Issue 7 (July 2019) - Wan, Weifeng; Ding, Yan; Xie, Zongyi; Li, Qian; Yan, Feng; Budbazar, Enkhjargal; Pearce, William J; Hartman, Richard; Obenaus, Andre; Zhang, John H; Jiang, Yong; Tang, Jiping
Platelet-derived growth factor receptor-β (PDGFR-β) has been reported to promote phenotypic transformation of vascular smooth muscle cells (VSMCs). The purpose of this study was to investigate the role of the PDGFR-β/IRF9/SIRT-1/NF-κB pathway in VSMC phenotypic transformation after subarachnoid hemorrhage (SAH). SAH was induced using the endovascular perforation model in Sprague-Dawley rats. PDGFR-β small interfering RNA (siRNA) and IRF9 siRNA were injected intracerebroventricularly 48 h before SAH. SIRT1 activator (resveratrol) and inhibitor (EX527) were administered intraperitoneally 1 h after SAH induction. Twenty-four hours after SAH, the VSMC contractile phenotype marker α-smooth muscle actin (α-SMA) decreased, whereas the VSMC synthetic phenotype marker embryonic smooth muscle myosin heavy chain (Smemb) increased. Both PDGFR-β siRNA and IRF9 siRNA attenuated the induction of nuclear factor-κB (NF-κB) and enhanced the expression of α-SMA. The SIRT1 activator (resveratrol) preserved VSMC contractile phenotype, significantly alleviated neurological dysfunction, and reduced brain edema. However, these beneficial effects of PDGFR-β siRNA, IRF9 siRNA and resveratrol were abolished by the SIRT1 inhibitor (EX527). This study shows that PDGFR-β/IRF9/SIRT-1/NF-κB signaling played a role in the VSMC phenotypic transformation after SAH. Inhibition of this signaling cascade preserved the contractile phenotype of VSMCs, thereby improving neurological outcomes following SAH.